The Influence Of Work Discipline, Work Motivation, And Work Environment On Employee Performance At UD. Karya Jati - Ridwan Mahmud; Budi Prabowo (UNIVED Press, 2024)
This study is used to test the influence of Work Discipline, Work Motivation, and Work Environment on Employee Performance at UD. Karya Jati. The method used is a quantitative method using primary and secondary data. The number of samples in this study is 48 respondents. Data were analyzed using SPSS software, and the analysis conducted includes validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination, F test, and t test. The research results show that (1) simultaneously, work discipline, work motivation, and work environment have a positive and significant effect on employee performance with a significance of 0.001 < 0.05. Partially, (2) work discipline has a positive and significant effect on employee performance with a significance of 0.014 < 0.05, (3) work motivation does not have a significant effect on employee performance with a significance of 0.106 > 0.05, and (4) work environment has a positive and significant effect on employee performance with a significance of 0.003 < 0.05. Based on research findings, it is recommended that UD. Karya Jati implement stricter sanctions against employees who violate industry regulations. Not only that, increasing employee motivation, such as by providing social security benefits, and paying more attention to workplace safety and comfort with the aim of improving their performance.